Progression and associated factors of lacquer cracks/patchy atrophies in high myopia: the Beijing Eye Study 2001-2011 : retinal disorders - Jonas, Jost B.; Xu, Liang; Wei, Wen Bin; Jonas, Rahul A.; Wang, Ya Xing (Graefe's archive for clinical and experimental ophthalmology, 2022)
Purpose: To assess the development and progression of lacquer cracks/patchy atrophies (LCs/PAs) in high myopia. Methods: The case control study included highly myopic eyes (refractive error ≤  − 6.0 diopters), examined in the population-based Beijing Eye Study 2001/2011. Using fundus photographs taken in 2001 and 2011 and optical coherence tomographic images obtained in 2011, we assessed the incidence and enlargement of pre-existing LC/PAs. Results: The study included 89 highly myopic eyes (age: 65.0 ± 9.4 years). Newly developed or enlarged LC/PAs were detected in 17 (19.1%; 95% confidence interval (CI): 11.0, 27.0) eyes, with a new LC development without previous LCs, enlargement of a pre-existing LC, LC enlargement to a PA, development of a new PA without any previous LCs, and enlargement of a pre-existing PA detected in 3, 3, 5, 3, and 3 eyes, respectively. In 14 (82.4%; 95%CI: 62.3, 100) of the 17 eyes with LC/PA development or enlargement, the LC/PAs elongated perpendicularly to, and widened in, the direction of gamma zone enlargement. Higher prevalence of LC/PA enlargement was associated (multivariable analysis) with higher myopic maculopathy stage in 2001 (odds ratio (OR): 7.83; 95%CI: 2.65, 23.2; P < 0.001) and higher frequency of parapapillary delta zone enlargement (OR: 32.0; 95%CI: 3.07, 334; P < 0.001). Prevalence of LC/PA enlargement was lower than the prevalence of changes in other myopic maculopathy features (disc-fovea distance elongation: 71%; choroidal vessel shift: 55%; reduction in ophthalmoscopical disc size: 34%; ophthalmoscopic disc size enlargement: 25%). All eyes with LC/PA enlargement showed a pre-existing and enlarging gamma zone. Conclusions: Development and enlargement of LC/PAs were associated with enlargement of parapapillary delta zone and often occurred in association with the direction of gamma zone enlargement.
Gesehen am 14.08.2023